Comparison of long-term outcomes of complete vs. incomplete revascularization in elderly patients (≥75 years) with acute coronary syndrome and multi-vessel disease undergoing percutaneous coronary intervention - Lu, Yu-Ying; Lee, Chen-Hung; Chen, Chun-Chi; Chen, Dong-Yi; Ho, Ming-Yun; Yeh, Jih-Kai; Huang, Yu-Chang; Chang, Chieh-Yu; Wang, Chao-Yung; Chang, Shang-Hung; Hsieh, I-Chang; Hsieh, Ming-Jer (Frontiers in Cardiovascular Medicine, 2023)
Background The optimal revascularization strategy for elderly patients with acute coronary syndrome remains uncertain. The aim of this study is to assess the effect of complete revascularization (CR) and incomplete revascularization (IR) on long-term outcomes in elderly with acute coronary syndrome and multivessel disease. Methods This propensity-score matched cohort study was conducted using registry data from 2011 to 2019. Elderly (≥75 years) with acute coronary syndrome and multivessel disease who received percutaneous coronary interventions were divided into CR and IR groups according to angiography at the index hospitalization. Major adverse cardiovascular events (MACEs) were a composite of all-cause mortality, recurrent non-fatal myocardial infarction, and any revascularization at 3 years of follow-up. Results A total of 1018 patients were enrolled, of whom 496 underwent CR (48.7%) and 522 patients underwent IR (51.3%). After 1:1 propensity-score matching, 395 pairs of patients in matched cohorts were analyzed. After 3 years of follow-up, CR was significantly associated with a lower risk of MACEs (16.7% vs 25.6%, HR = 0.65, 95% CI: 0.47–0.88, p = 0.006) than IR, mainly driven by all-cause mortality. The trend of a better reduction in the risk of MACEs in CR than in IR was consistent across all pre-specified subgroups, but there was a greater benefit in the patients with ST segment elevation. Conclusion Complete revascularization was associated with a lower risk of 3-year MACEs than incomplete revascularization, and it can be recommended for elderly with acute coronary syndrome and multivessel disease, especially who presented with ST segment elevation.